LEGAL PROTECTION FOR WAGED WORKERS UNDER THE MINIMUM WAGE AT THE REGENCY/MUNICIPALITY LEVEL - Santjoko, Muhammad Widhijanto; Suroso, Dr. Imam (Acitya Wisesa: Journal of Multidisciplinary Research, 2024)
Wages have always been a common issue between workers and businesses because it involves a civil legal relationship that is regulated through an employment contract. The government mediates between the two parties by regulating the minimum wage, which is the responsibility of the governor in each province. Contravention of minimum wage provisions is considered a criminal offense, even though the relationship was originally intended as a civil one, and this research examines whether the policy is appropriate. This research finds and describes the provisions of the labor agreement and the ideal policy regarding the payment of wages under the minimum wage. This research uses a normative legal approach that focuses on the concepts of decriminalization and depenalization related to the payment of wages under the minimum wage. The approach used includes conceptual and statutory approaches, connecting labor law with criminal law and agreements. The sources of legal materials used include labor-related laws and legal literature, with analysis based on relevant articles. Therefore, employers, both civil legal entities and individuals, are prohibited from paying wages under the minimum wage according to Article 88E (2) of Law No. 6/2023. If violated, employers may be subject to imprisonment of up to 4 years and a fine of IDR 400 million under Article 185. This provision aims to protect workers' rights to a decent wage in each regency/ municipality.